An expert system as a support to the decision making process for groundwater management of alluvial groundwater bodies in Slovenia - Souvent, Petra; Vižintin, Goran; Celarc, Sašo; Čenčur Curk, Barbara (Geologija, 2014)
The expert decision support system for groundwater management in the shallow alluvial aquifers links numerical groundwater flow models with the water permits and concessions databases in order to help groundwater managers to quantify sustainable yield for a given groundwater body and provide additional information for sustainable groundwater management. Stand alone numerical groundwater models are used in the process of the assessment of groundwater quantitative status as well as for assessing local yield quantity during the period of maximum water demand and minimum groundwater recharge.